Development and Validation of Teachers’ Practices on Formative Assessment Scale (TPFAS): A Measure Using Feedback Loop Model - Ole, Faith Celeste (International Journal of Education, 2020)
This study aimed to develop and validate an instrument regarding teachers’ practices on formative assessment using the elements of the Feedback Loop Model. A pilot study was surveyed to 157 science teachers on how frequently they practice formative assessments in their Science classes. Teachers’ responses were analyzed using Cronbach’s alpha statistics on the Feedback Loop constructs and Confirmatory factor analysis for the entire instrument. Findings suggest that with the deletion of 10 survey items from the initial 44 items, the scale provides a valid and highly reliable measure in determining teachers’ practices on formative assessment.